2021
DOI: 10.1101/2021.11.08.467773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A self-amplifying mRNA COVID-19 vaccine drives potent and broad immune responses at low doses that protects non-human primates against SARS-CoV-2

Abstract: The coronavirus disease 2019 (COVID-19) pandemic continues to spread globally, highlighting the urgent need for safe and effective vaccines that could be rapidly mobilized to immunize large populations. We report the preclinical development of a self-amplifying mRNA (SAM) vaccine encoding a prefusion stabilized severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike glycoprotein and demonstrate potent cellular and humoral immune responses at low doses in mice and rhesus macaques. The homologous prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…6, 57 AAHI-SC2 appears to elicit strong T cell responses in preclinical studies, possibly due to the combination of the adjuvanting properties of squalene and saRNA, and may provide a foundation for durable and long-term T-cell immunity. Upcoming studies in non-human primates and clinical trials in humans should provide additional data to evaluate the immunogenicity, and particularly the T cell induction, of AAHI-SC2 for comparison to published data on mRNA-1273, BNT162b2, and other SARS-CoV-2 mRNA 6, 7, 58 or saRNA 24, 25, 27, 29, 30 vaccines in development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6, 57 AAHI-SC2 appears to elicit strong T cell responses in preclinical studies, possibly due to the combination of the adjuvanting properties of squalene and saRNA, and may provide a foundation for durable and long-term T-cell immunity. Upcoming studies in non-human primates and clinical trials in humans should provide additional data to evaluate the immunogenicity, and particularly the T cell induction, of AAHI-SC2 for comparison to published data on mRNA-1273, BNT162b2, and other SARS-CoV-2 mRNA 6, 7, 58 or saRNA 24, 25, 27, 29, 30 vaccines in development.…”
Section: Discussionmentioning
confidence: 99%
“…Self-amplifying RNA (saRNA) vaccines-in which RNAs encode viral replicase genes in addition to antigen genes-promise improved potency and durability due to both the amplification of the RNA in vivo after delivery and the adjuvanting properties of dsRNA and replication intermediates. 11,22,23 Indeed, saRNAs have been successfully used to create COVID-19 vaccines [24][25][26][27][28][29][30] that have reached clinical trials. 31,32 However, thermostability of these vaccine formulations is either unknown 24,25,[27][28][29][30] or 1 week at refrigerated or room-temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This approach differs from the one used by Shattock et al in their preclinical and unsuccessful clinical trial. 25,26 Recent COVID-19 saRNA vaccine preclinical research 16,[26][27][28][29][30][31] supports the hypothesis that, because of their replicon features, saRNA vaccines are able to induce equivalent or more potent immune responses at lower doses compared to those achieved by non-replicating mRNA vaccines. 3,6 In our study, we confirm this hypothesis and find that multi-antigenic immunization of mice with only 1 mg of the ZIP1642 vaccine was able to induce 100% seroconversion toward high binding GMT values that elicited neutralizing activity against three different SARS-CoV-2 variants (Wuhan, Beta, and Delta variants) that was considerably higher than the neutralizing titers found in the sera of convalescent COVID-19 patients.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, it can be said that SAM vaccines have shown their immunogenic potency against multiple targets [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. In addition, based on preclinical data, it can be concluded that SAM-mRNA vaccines could potentially induce a more durable immune response compared to non-replicating mRNA vaccines [ 53 ].…”
Section: Mrna Vaccinementioning
confidence: 99%